CLINICAL AND LABORATORY CHARACTERISTICS OF TROPHIC ULCER OF THE ORAL CAVITY - Kamilov Khaidar Pazilovich; Saparov Akbar Bakhodirovich (Modern American Journals, 2025)
Modern diagnostics of trophic ulcers of the oral mucosa is based on a comprehensive approach, including clinical examination, laboratory methods, instrumental and morphological studies. Treatment of trophic ulcers of the oral mucosa is a complex clinical task and requires a comprehensive, pathogenetically substantiated approach. It includes the elimination of etiological factors, systemic therapy of the underlying disease, local treatment of the ulcer defect, as well as the use of regenerative and immunomodulatory agents. This article describes the results of studies conducted after the treatment of trophic ulcers of the oral mucosa using Novacell Ziyo biofilm (Uzbekistan)
Keywords: Trophic ulcer, oral mucosa, treatment, biofilm.